What static and dynamic properties should slalom skis possess? Judgements by advanced and expert skiers - Fischer, C.; Overney, L. S.; Fauve, M.; Blanke, O.; Rhyner, H.; Herzog, M. H.; Bourban, P.-E.; Manson, J. A. E. (Journal of Sports Sciences, 2007)
Flexural and torsional rigidity are important properties of skis. However, the flexural and torsional rigidity that lead to optimal performance remain to be established. In the present study, four pairs of slalom skis that differed in flexural and torsional rigidity were tested by advanced and expert skiers. Using a 10-item questionnaire, different aspects of the skis' performance were rated on a 9-point scale. For each pair of skis, physical measurements were compared with the ratings of the two groups of skiers. Correlations (Spearman) were then determined between (i) different mechanical properties of the skis (static and dynamic), (ii) subjective assessments of the participants, and (iii) properties of the skis and the participants' assessments. The latter showed that expert skiers rate the aspects of the skis more accurately than advanced skiers. Most importantly, expert skiers are particularly sensitive to torsion of the skis. These results suggest that such highly rated elements should be addressed in future ski designs.